2003
DOI: 10.2519/jospt.2003.33.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Rearfoot Asymmetry and Anterior Knee Pain Syndrome

Abstract: Study Design: Single-session observational study. Objectives: To examine the magnitude and extent of asymmetry between right and left rearfoot angles in individuals who are asymptomatic versus symptomatic for anterior knee pain. Background: Asymmetry in lower limb measures has been linked to the occurrence of knee pathologies, yet the practice of deriving unilateral rather than bilateral data and thereafter averaging the findings may play a role in obscuring the true nature of the rearfoot angle-knee pain rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 39 publications
1
21
1
3
Order By: Relevance
“…This finding is in agreement with other studies, which found no difference between rearfoot posture in stance and the occurrence of PFPS 9,13,18 . Although the reliability of the rearfoot angle found in the present study was excellent, previous reports of reliability have been poor for this measure 29 .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This finding is in agreement with other studies, which found no difference between rearfoot posture in stance and the occurrence of PFPS 9,13,18 . Although the reliability of the rearfoot angle found in the present study was excellent, previous reports of reliability have been poor for this measure 29 .…”
Section: Discussionsupporting
confidence: 83%
“…A systematic review, which evaluated risk factors associated with PFPS, stated that the actual knowledge is still insufficient to confirm the relationship between rearfoot alignment and this dysfunction, therefore, more evidences need to be established 19 . Although widely recommended in clinical practice and in theoretical thought 1,[5][6][7] , the scientific basis for the association of rearfoot and Q angles with PFPS is still controversial 8,9,19 . Studies with a sample size large enough to allow inferences from the results are necessary to investigate the association between clinical static measures and PFPS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural anomalies and lower extremity malalignment are often examined as associative factors for PFPS in case-control studies. 1,[25][26][27]31 In the literature, female gender is often suggested to be a risk factor for PFPS. 13,21,33,43 Findings of 1 prospective study included in this review support the notion that females are at higher risk for PFPS than males.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] Conversely, measuring the uninjured (retrospectively) or only a representative side (prospectively) also has been questioned, because studies of isolated anatomic factors have indicated that bilateral symmetry cannot always be assumed. [15][16][17] However, there remains a paucity of data that has critically examined the prevalence and magnitude of bilateral asymmetries in lowerlimb anatomic characteristics to aid clinicians and researchers in making these determinations.…”
Section: Introductionmentioning
confidence: 99%